Respuestas
Respuesta dada por:
1
1) 7x-5x=54
2x=54
==3) 6x-4x= 26+42
2x = 68
= x =68:2
x=54:2
x=27
/ x= 34
2)5x-3x=-26-22
2x = - 48
x = -48: 2
x= -24
2x=54
==3) 6x-4x= 26+42
2x = 68
= x =68:2
x=54:2
x=27
/ x= 34
2)5x-3x=-26-22
2x = - 48
x = -48: 2
x= -24
Respuesta dada por:
0
1)7x-54=5x
7x-5x=54
2x=54
x=27
2)5x+22=3x-26
5x-3x=-26-22
2x=-48
x=-24
3)6x-41=4x+26
6x-4x=26+41
2x=67
x=67/2
7x-5x=54
2x=54
x=27
2)5x+22=3x-26
5x-3x=-26-22
2x=-48
x=-24
3)6x-41=4x+26
6x-4x=26+41
2x=67
x=67/2
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 10 años